Atención de pacientes sometidos a cirugía electiva de vías biliares en dos instituciones del segundo nivel de atención en salud, 1995 (1997)
ABSTRACT: This project is framed within two research lines. The first one is about health care assistance, and the second about nursing practice. The assistance to patients under bile duct elective surgery was selected because of its second place in the digestive tract surgeries after the gastroduodenal ulcer, and the second level health institutions because of their process of improving the quality of the services. These institutions have shown interest in evaluating the health care assistance, taking into consideration the demand of their surgical services. Therefore, the nursing departments need the implementation of high quality health care and models in order to benefit the users and the protocols and the qualification of the nursing sci&tech function. It was concluded that there are limitations in the efficiency of the health institutions in terms of planning and management, lack of nursing professional personnel, and structural deficiencies in nursing working places. The nursing personnel have delegated its basic function related to the care and education of patients under surgery. It is evident the inclusion of ambulatory programs via laparoscopically. Moreover, a serious complication in the evolution of patient was found. Finally, the doubts stated by the patient and family in terms of post-surgery care at home were written down.